APLIKASI PENGAJUAN KOMPLAIN NASABAH BANK MELALUI NOTIFIKASI WHATSAPP - Imam Solikin; Mutiara Mutiara (Universitas Methodist Indonesia, 2023)
During the covid 19 pandemic, the use of website technology facilities is very important because it reduces direct interaction between banks and customers to prevent the spread of covid 19. PT Bank Pembangunan Daerah Sumatera Selatan and Bangka Belitung were established on November 6, 1957 under the name PT Bank Pembangunan South Sumatra. Complaints faced by Bank Sumsel Babel from customers such as money not being received but debited account, insufficient money received, not making a transaction but account being debited twice, failed transfer to another bank, debited account, transfer via M-Banking failed to debit account, etc. The Complaint Process for South Sumatra Babel customers now has to come directly to the office, customers will take a long time if they are far from the Bank Sumsel office, Customers queue for a long time and have to complete the file manually (physically). The solution to overcome these problems is to build a Customer Complaint File Submission Service system at Bank Sumsel which can be accessed online with the results of the notification of the resolution of the problem obtained by the customer via WhatsApp. This can provide service quality and customer satisfaction. The system development method used is the waterfall model. The purpose of this study is to build an information system for filing complaints at Bank Sumsel Babel which will make it easier to process data for filing complaints